2018
DOI: 10.2337/db18-0355
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in White Blood Cell, Neutrophil, and Red Blood Cell Counts Related to Sex, HLA, and Islet Autoantibodies in Swedish TEDDY Children at Increased Risk for Type 1 Diabetes

Abstract: Islet autoantibodies (IAs) precede the clinical onset of type 1 diabetes (T1D); however, the knowledge is limited about whether the prodrome affects complete blood counts (CBCs) in 4- to 12-year-old children with increased genetic risk for T1D. This study tested whether CBCs were altered in 4- to 12-year-old children without ( = 376) or with one or several IAs against insulin, GAD65, or IA-2 ( = 72). CBC was analyzed during longitudinal follow-up in 448 Swedish children enrolled in The Environmental Determinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 49 publications
2
19
0
1
Order By: Relevance
“…Although we found differences in gender proportions between groups, HLA risk assessment usually does not differ between males and females. One study in children at risk of T1D found an association between gender and HLA risk alleles DRB1*03/DRB1*04 and islet autoimmunity 34 . This is probably not relevant in our population, as we included only individuals with T1D older than 13 years.…”
Section: Discussionmentioning
confidence: 99%
“…Although we found differences in gender proportions between groups, HLA risk assessment usually does not differ between males and females. One study in children at risk of T1D found an association between gender and HLA risk alleles DRB1*03/DRB1*04 and islet autoimmunity 34 . This is probably not relevant in our population, as we included only individuals with T1D older than 13 years.…”
Section: Discussionmentioning
confidence: 99%
“…The highest-frequency detection of all three types of DAA was diagnosed in the DAA+ children group: IAA -in 149 (92.56%), GADAin 137 (84.61%), and IA-2A -in 23 The prospective pathogenetic priority of elevated IA-2A and GADA titers was determined comparing to IAA content at the preclinical and early clinical stages of T1D development in DAA+ children and adolescents. The significantly highest titers of IAA, GADA, and IA-2A compared with titers of DAA+ children at early stage of T1D development and DAA levels of children with a clinical debut of disease, respectively, were noted in the group of DAA+ children at late latent stage of T1D development, approximate in time to the clinical debut of disease [24][25][26]. The reduced frequency detection of DAA and the lower values of their levels were registered by us in children with newly detected T1D compared with the group of DAA+ children at the late preclinical stages of disease development confirms the completion of autoimmune destruction for desensitizing autoantigens, and, as a result, a decrease in previously elevated DAA titers, which is confirmed in recent publications [17,[22][23][24][25].…”
Section: Resultsmentioning
confidence: 97%
“…ISSN 1680-1466' ENDOKRYNOLOGIA' 2019, VOLUME 24,No. 3 Thus, the highest values of elevated IA-2A and GADA titers were determined in the group of DAA+ children both at baseline and in the final of the preclinical stage of T1D development, and the maximum increase of IA-2A and GADA titers was detected in the finale of preclinical stage of T1D development in DAA+ children and adolescents in whom the disease manifestation occurred within the first three years after the establishing DAA-positive status, which allows us quite accurately predict the time of clinical debut of T1D in DAA+ children [26]. Thus, it was found that the prevalence of tandemsimultaneous combination increasing the autoantibody titers -IA-2A and GADA has a pathogenetic priority importance during the evolution of T1D latent stage, which is consistent with the data of other authors [16,23,[27][28][29].…”
Section: оригінальні дослідженняmentioning
confidence: 99%
“…Moreover, the increase of neutrophils in pancreas of T1D organ donors concomitantly correlates with the reduction of peripheral blood circulating neutrophils, thus leading to the hypothesis of a pancreas‐centred massive migration (tissue sequestration) of these cells under specific pathological conditions. Such reduction has been recently highlighted also in another longitudinal T1D study cohort (TEDDY), which observed a significant reduction of peripheral blood circulating neutrophils in at‐risk children positive for multiple islet autoantibodies, therefore indirectly corroborating the hypothesis of neutrophils massive migration to the pancreas . Although the evidence for a role of neutrophils is increasingly important, additional studies are needed to decipher a mechanistic link between neutrophils migration to the pancreas and triggering or amplification of autoimmunity in T1D.…”
Section: Innate Immune Cells: Novel Players In T1d Pathogenesismentioning
confidence: 99%